Success of 6-mm Implants with Single-Tooth Restorations: A 3-year Randomized Controlled Clinical Trial. (June 2016) - Sahrmann, P.; Naenni, N.; Jung, R.E.; Held, U.; Truninger, T.; Hämmerle, C.H.F.; Attin, T.; Schmidlin, P.R.
The aim of the study was to test whether implants of 6 mm in length perform equally well as 10-mm implants in terms of survival and marginal bone-level changes when supporting single crowns. Patients with a posterior single-tooth gap were randomly allocated to either the placement of a 6-mm (test) or 10-mm implant (control). The treatment protocol allowed for internal sinus lift but not for lateral bone augmentation. After a healing period of 10 wk, implants were loaded with screw-retained single crowns. Survival rates, number of pockets ≥5 mm, and bleeding-on-probing were assessed clinically. The change of marginal bone level and crown-to-implant ratios were analyzed by 2 examiners. Longitudinal intragroup analyses for marginal bone levels were performed applying the Wilcoxon signed rank test. Intergroup differences at baseline and at 3 y were compared using the Mann-Whitney U test. The effect of implant length and crown-to-implant ratio on changes of marginal bone level also was determined. Of 94 implants placed (47 test and 47 control), 78 implants (40 test and 38 control) were available for follow-up examination at 3 y of loading. One test implant was lost during the second year. Hence, implant survival was not significantly different between the 2 groups after 3 y (98% test; 100% control). We found no significant change in the crestal bone level from baseline to 3 y for test and control implants with −0.19 ± 0.62 mm and −0.33 ± 0.71 mm, respectively. The intergroup difference was not significant. Crown-to-implant ratios were not associated with a statistically significant difference in marginal bone loss. However, the number of sites with pockets ≥5 mm was significantly higher in the test group. Based on the 3-y assessment, the use of 6-mm implants can be considered a viable option when reconstructing posterior single tooth gaps (German Clinical Trials Registry: DRKS00006290).